có ai giúp mình với \(\frac{6^3+3\cdot6^2+3^2}{-13}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1 :
\(\frac{2}{1\cdot3}+\frac{2}{3\cdot5}+\frac{2}{5\cdot7}+...+\frac{2}{\left(2x+1\right)\left(2x+3\right)}=\frac{9}{19}\)
\(\Leftrightarrow1-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{2x+1}-\frac{1}{2x+3}=\frac{9}{19}\)
\(\Leftrightarrow1-\frac{1}{2x+3}=\frac{9}{19}\)
\(\Leftrightarrow\frac{1}{2x+3}=1-\frac{9}{19}\)
\(\Leftrightarrow\frac{1}{2x+3}=\frac{10}{19}\)
\(\Leftrightarrow10.\left(2x+3\right)=19\Leftrightarrow2x+3=\frac{19}{10}\)
\(\Leftrightarrow2x=\frac{19}{10}-3\Leftrightarrow2x=-\frac{11}{10}\)
\(\Leftrightarrow x=-\frac{11}{20}=-0,55\)
Bài 2 :
\(\frac{2}{2.4}+\frac{2}{4.6}+\frac{2}{6.8}+...+\frac{2}{2016.2018}\)
\(=\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{6}+\frac{1}{6}-\frac{1}{8}+....+\frac{1}{2016}-\frac{1}{2018}\)
\(=\frac{1}{2}-\frac{1}{2018}=\frac{504}{1009}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{6^3+3.6^2+3}{-13}\)
\(=\frac{216+108+27}{-13}\)
\(=\frac{351}{-13}\)
\(=-27\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{6^3+3.6^2.3^3}{-13}\)
\(=\frac{3^3.2^3+3.3^2.2^2.3^3}{-13}\)
\(=\frac{3^3.2^2.\left(2+3^3\right)}{-13}\)
\(=\frac{3^3.2^2.54}{-13}\)
\(=>....\)
\(\frac{6^3+3\cdot6^2\cdot3^3}{-13}\)
\(=\frac{216+3\cdot36\cdot27}{-13}\)
\(=\frac{216+2916}{-13}\)
\(=\frac{3132}{-13}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{4.5.6}{14.15.16}\)=\(\frac{1.1.3}{7.3.4}\)=\(\frac{1.1.1}{7.1.4}\)=\(\frac{1}{28}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{6^3+3\cdot6^2+3^3}{-13}\)
\(=\frac{6^2\cdot\left(6+3\right)+3^3}{-13}\)
\(=\frac{6^2\cdot3^2+3^3}{-13}\)
\(=\frac{3^3\cdot\left(6^2+3\right)}{-13}\)
\(=\frac{3^3\cdot39}{-13}\)
\(=-3^3=-27\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\dfrac{3^2\left(2^2+2^3+1\right)}{-13}=\dfrac{-13\cdot3^2}{13}=-9\)
\(\frac{6^3+3.6^2+3^2}{-13}\)
\(=\frac{\left(2.3\right)^3+3.\left(2.3\right)^2+3^2}{-13}\)
\(=\frac{2^3.3^3+\left(3.3^2\right).2+3^2}{-13}\)
\(=\frac{3^2.\left(2^3.3+3.2+1\right)}{-13}\)
\(=\frac{3^2.31}{-13}\)
\(=\frac{9.31}{-13}\)
\(=\frac{273}{-13}\)
\(=-21\)